Alternatif Manajemen Kapasitas Proyek Peningkatan Struktur Jalan Labuhan Sreseh Kabupaten Sampang - Mukti, Hazin; Zabadi, Fairus (Sekolah Tinggi Teknologi Dumai, 2024)
Capacity is a breakthrough or a number of units that a facility can storage, receive, or produce in a particular time period. Capacity often determines the need for capital and therefore large fixed costs. This research uses quantitative methods. There is an effect of capacity planning variables (x1) on capacity management (y) with gis value. 0.012 < 0.05 and t_calculated value 2.694 > 2.056. There is an influence of capacity implementation variables (x2) on capacity management (y) with sig value. 0.000 < 0.05 and t_calculated value 5.101 > 2.056. There is no influence of capacity monitoring variables (x3) on capacity management (y) with sig value. 0.659 > 0.05 and t_calculated value -.447 < 2.056. The variable or indicator that most dominantly influences capacity management is capacity implementation (x2) with a value of 5.101. There is a similar influence of all variables on capacity management. With f value of 44.028 > 2.96 in gis. 0.000 < 0.05. R square results of 0.836, can mean that 83.6% of capacity management is influenced by all variables.